2011
DOI: 10.1002/ejoc.201100859
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 4′‐C,3′‐O‐Propylene‐Linked Bicyclic Nucleosides

Abstract: A set of pyrimidine nucleosides fused with a 4′‐C,3′‐O‐propylene bridge was successfully synthesised in 12 steps from 1,2:5,6‐di‐O‐isopropylidene‐α‐D‐glucofuranose, an inexpensive starting material, based on a ring‐closing metathesis (RCM) reaction followed by Vorbrüggen‐type nucleobase coupling. Antiviral and cytotoxicity activities of the targeted modified nucleosides, as well as their phosphoramidate prodrugs, are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Nucleoside analogs. Nucleoside derivatives (designated compounds 1 to 14) were synthesized in our laboratory according to previously reported procedures (29,(40)(41)(42)(43)(44)(45) and were at least 95% pure, as estimated by liquid chromatography-mass spectrometry (LC-MS) and nuclear magnetic resonance (NMR) analyses. Chemical structures for compounds 1 to 14 are summarized in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleoside analogs. Nucleoside derivatives (designated compounds 1 to 14) were synthesized in our laboratory according to previously reported procedures (29,(40)(41)(42)(43)(44)(45) and were at least 95% pure, as estimated by liquid chromatography-mass spectrometry (LC-MS) and nuclear magnetic resonance (NMR) analyses. Chemical structures for compounds 1 to 14 are summarized in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…223 While the cytosine analog 450a was hydrogenated with hydrogen over Pd/C, the uracil derivative 450b was hydrogenated by transfer hydrogenation over Pd/C to minimize the simultaneous uracil base hydrogenation.…”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%
“…Similarly, Hatton et al reported the reduction of the 4′- C -3′- O -propylene-linked bicyclic pyrimidine nucleoside (Scheme 134 ). 223 While the cytosine analog 450a was hydrogenated with hydrogen over Pd/C, the uracil derivative 450b was hydrogenated by transfer hydrogenation over Pd/C to minimize the simultaneous uracil base hydrogenation.…”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%